Increased plasma D-dimer levels may be a promising indicator for diabetic peripheral neuropathy in type 2 diabetes - Zhuang, Lei; Yu, Chao; Xu, Feng; Zhao, Li-hua; Wang, Xiao-hua; Wang, Chun-hua; Ning, Li-yan; Zhang, Xiu-lin; Zhang, Dong-mei; Wang, Xue-qin; Su, Jian-bin (Frontiers in Endocrinology, 2022)
Background: Increased plasma D-dimer levels have been reported to be associated with a range of adverse health outcomes. This study aimed to determine whether plasma D-dimer is connected to diabetic peripheral neuropathy (DPN) in patients with type 2 diabetes (T2D). Methods: This study was part of a series exploring the potential risks for DPN. All patients were questioned for neurologic symptoms, examined for neurologic signs and received nerve conduction studies to collect nerve action potential onset latency, amplitude and conduction velocity (NCV). Composite Z scores of latency, amplitude and NCV were calculated. DPN was confirmed as both at least a neurologic symptom/sign and an abnormality of nerve conduction studies. Coagulation function indices, such as plasma D-dimer levels, were also synchronously detected. Results: We finally recruited 393 eligible patients for this study, of whom 24.7% (n=97) were determined to have DPN. The plasma D-dimer level was found to be closely associated with the composite Z score of latency, amplitude and NCV after adjusting for other coagulation function indices and clinical covariates (latency: β=0.134, t=2.299, p=0.022; amplitude: β=–0.138, t=–2.286, p=0.023; NCV: β=–0.139, t=–2.433, p=0.016). Moreover, the prevalence of DPN in the first, second, third and fourth quartiles (Q1, Q2, Q3 and Q4) of the D-dimer level was 15.2%, 15.9%, 26.4% and 42.7%, respectively (p for trend<0.001). The corresponding adjusted odds ratios and 95% CIs for DPN in D-dimer quartiles were 1, 0.79 (0.21–2.99), 1.75 (0.49–6.26) and 5.17 (1.38–19.42), respectively. Furthermore, the optimal cut-off value of the plasma D-dimer level to discriminate DPN was ≥0.22 mg/L (sensitivity=67.01%, specificity=58.78% and Youden index=0.26) after analysis by receiver operating characteristic curve. Conclusions: Increased plasma D-dimer levels may be a promising indicator for DPN in patients with T2D.